Up regulation of nitric oxide synthase–nitric oxide system in the testis of rats undergoing autoimmune orchitis - Jarazo Dietrich, Sabrina Soledad (2012)
Background: Male reproductive tract infection and inflammation are important aetiological factors of infertility. Experimental Autoimmune Orchitis (EAO) is a model of chronic inflammation useful to study mechanisms of inflammatory reactions leading to testicular impairment. EAO is characterised by interstitial cell infiltrate of lymphomonocytes, producers of pro-inflammatory cytokines involved in germ cell apoptosis. Nitric oxide (NO), a free radical promoting immune cell activation and apoptosis, is synthesised by conversion of l-arginine to l-citrulline catalysed by NO synthase (NOS). The NOS isoforms are: constitutively endothelial (e) and neuronal (n) NOS and inducible (i) NOS. Objectives: Although the NO–NOS system was found to be up-regulated by pro-inflammatory mediators in immune and non immune testicular cells, data on its regulation in chronic inflammatory states is lacking. Methods and results: EAO was induced in rats by active immunisation with spermatic antigens and adjuvants; control (C) rats were injected with adjuvants. Untreated normal (N) rats were also studied. We demonstrated that iNOS, eNOS and nNOS was mainly expressed by interstitial cells in N and C rats and that in EAO NOS was up-regulated and also expressed by tubular cells. Constitutive and inducible NOS content (Western blot) as well as NO production and activity increased in the testis of rats with EAO. iNOS content and activity were selectively up-regulated in the testis of rats with orchitis. Flow cytometric analysis of NOS isoforms in testicular macrophages (M) showed that the percentage of ED1+ED2− and ED1+ED2+ M subsets, expressing constitutive and iNOS isoforms was significantly higher in EAO, but no change in the percentage of ED1−ED2+ resident M was observed compared to C rats. M from EAO rats also released more NO than C and N rats. Conclusions: In testis of rats with EAO, NO–NOS system was up-regulated and both testicular M and cells from seminiferous tubules contributed to NO increase. NO over production in orchitis was generated mainly by increased iNOS content and activity.